A intervenção docente no processo de produção textual: uma análise sobre as práticas de professores em formação inicial do curso de Língua Portuguesa - BARBOSA, Patrícia Negrão (2020)
For a long time primary and high school students have shown difficulties in using written language to express themselves. However, this difficulty to write is not only the students‟. The teacher also encounters difficulties, but on the other side of the writing process. This is, in the process of correction of texts produced in the classroom. In this sense, to understand how teachers in training intervene in the texts of the students, we performed a qualitative-interpretative research of ethnographic and applied nature, whose general objective was "to reflect on the process of textual production intervened by the mediators, teachers in training " and the specific objectives were: to identify the types of intervention carried out in the students‟ texts; verify that the modifications were made by the students after the interventions; and check the language used by the teachers in training during the intervention. In order to achieve our objectives, we developed, during the discipline of Supervised Internship in High School, the application of a Didactic Sequence (DS) in a mini-course format, in a state school in Castanhal city, Pará. During the application, we made observations and notes about classroom activities related to DS activities, conversations with students and teachers, and selected texts for analysis. As a theoretical reference, we used Bakhtin (2014), Geraldi (2012), Passarelii (2012), Ruiz (2015), Sercundes (2004), Travaglia (1996), Menegassi (2010) as a base, among other authors. From the correction typologies presented by Ruiz (2015), we observed, during the data analysis, that the teachers used the indicative correction more frequently. As for the students' responses to the rewriting process, in most of the data the students sought to follow the corrections, but they showed difficulties in rewriting the text, leaving some problems uncorrected and made new errors in the rewritten texts. This led us to the conclusion that the difficulty in rewriting was related to the type of language used by the teachers in the correction process, since most of the information added in the texts were grammatical terms.